Optimizing The Implementation of Nursing Credentials: A Literature Review - Susanti, Ni Putu Aries; Susanti, NLP Dina; Wahyuningsih , Luh Gde Nita Sri; Agustini, Komang Tri (Babali Nursing Research, 2024)
Introduction: The credentialing process is a series of expertise verifications to obtain clinical authority, especially for nurses. This literature review aimed to gain further exposure to implementing nursing credentials and determine whether the implementation is optimal.Methods: The method used a literature review. Article searches were carried out via PubMed, Google Scholar, and Wiley using the keywords “nursing credential” while searching in English articles and the keyword “kredensial perawat” in an article in Bahasa. A total of fifteen articles were extracted based on the inclusion and exclusion criteria.Results: Nurses are expected to provide services by their clinical competence and authority through the credentialing process. Many studies showed that the implementation of credentials still needs to be improved. The main challenge found in many studies regarding the implementation of credentials is the overlapping of duties by the credentials committee. Conclusion: If the credentialing process is carried out correctly and optimally following existing laws and regulations, it will benefit nurses and hospitals significantly. These benefits include, among others, the fact that nurses can optimize the nursing care provided and provide legal protection because nurses have carried out competencies by their authority. Meanwhile, hospitals can improve the quality of service, maintain patient safety, and increase patient and family satisfaction.